2023
DOI: 10.3390/ijms24065690
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Neurotoxin A4 Has a 1000-Fold Reduced Potency Due to Three Single Amino Acid Alterations in the Protein Receptor Binding Domain

Abstract: Botulinum neurotoxin subtype A4 (BoNT/A4) is ~1000-fold less potent than BoNT/A1. This study addresses the basis for low BoNT/A4 potency. Utilizing BoNT/A1-A4 and BoNT/A4-A1 Light Chain-Heavy Chain (LC-HC) chimeras, HC-A4 was responsible for low BoNT/A4 potency. Earlier studies showed BoNT/A1-receptor binding domain (Hcc) bound a β-strand peptide (556–564) and glycan-N559 within Luminal Domain 4 (LD4) of SV2C, the BoNT/A protein receptor. Relative to BoNT/A1, the Hcc of BoNT/A4 possesses two amino acid variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The significant differences between BoNT/A3 and BoNT/A4 in binding affinity and cleavage efficiency particularly affects their S1’ subsite recognition [ 146 ]. Further functional and modelling studies indicated that in rodent models, the disruption of HCc-V2C β-peptide and -glycan-N559 interactions mediates low BoNT/A4 potency, while in human motor neurons, the disruption of HCc-SV2C β-peptide alone mediates low BoNT/A4 potency due to species-specific variation at the SV2C site [ 147 ].…”
Section: Exploration Of Therapeutic Potential Of Bonts Toxinotypes Or...mentioning
confidence: 99%
“…The significant differences between BoNT/A3 and BoNT/A4 in binding affinity and cleavage efficiency particularly affects their S1’ subsite recognition [ 146 ]. Further functional and modelling studies indicated that in rodent models, the disruption of HCc-V2C β-peptide and -glycan-N559 interactions mediates low BoNT/A4 potency, while in human motor neurons, the disruption of HCc-SV2C β-peptide alone mediates low BoNT/A4 potency due to species-specific variation at the SV2C site [ 147 ].…”
Section: Exploration Of Therapeutic Potential Of Bonts Toxinotypes Or...mentioning
confidence: 99%
“…However, studies have shown that the LC and H N domains of BoNTs are more immunogenic than the HC domains [ 66 , 110 ], suggesting that optimal vaccines should include these domains. Other studies have demonstrated that even if the H C is modified to lack ganglioside binding, it can still stimulate protective immunity in outbred mice [ 105 , 106 , 107 , 111 ], as well as that catalytic activity of the BoNT/LC can be diminished by introducing two to three single amino acid mutations that prevent coordination of the zinc in the LC [ 74 , 112 , 113 ]. This led to the idea of genetically inactivated holotoxin vaccines that are not able to produce toxicity but maintain their overall structure and immunogenicity.…”
Section: Recombinant Subunit and Toxin Vaccinesmentioning
confidence: 99%